Postop Spinal Fusion Pain and the Continued Neglect of Biopsychosocial Lens in Pediatric Orthopaedics - Young, Nicholas D.; Brimeyer, Chasity T. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
The recent JPOSNA® article by Younis et al.1 represents a troubling, antiquated lens on chronic pain following posterior spinal fusion (PSF) that perpetuates confusion about its etiology and undermines optimal evaluation, prevention, and management. Importantly, chronic pain does not occur in a physical vacuum – it is impossible to understand how chronic pain develops after surgery using a narrow focus on tissue, inflammatory processes, or mechanical complications alone. Instead, a biopsychosocial perspective is needed to more clearly understand the development/persistence of chronic pain and prevent acute pain from transitioning to chronic following surgery.2 In brief, a biopsychosocial conceptualization considers the combined and multi-directional contributions between biological (e.g., genetics, hormone abnormalities, comorbid disease, inflammatory response, nociception variation), psychological (e.g., premorbid psychiatric history, expectations, pain beliefs, maladaptive coping skills, thought patterns and perceptions, mood), and socioenvironmental components (e.g., extent of social support, socioeconomic factors, culture, health literacy, relationship with medical providers, interpersonal relationships). For example, pain catastrophizing (i.e., magnifying the threat of pain) and depressive symptoms can occasion persistent pain and undermine the course of recovery following musculoskeletal surgery.3 Persistent pain can lead to a sense of helplessness, social withdrawal, and worsening mood, which further perpetuates movement avoidance behaviors, deterioration of musculoskeletal tissue, and deconditioning.4 The biopsychosocial perspective is far from a novel concept across the extant literature. Bevers and colleagues highlighted that it has been “the most heuristic approach to chronic pain assessment, prevention, and treatment” since the 1970s.5 There is a wealth of knowledge in orthopaedic, rheumatologic, and neuro-mediated processes of pain, and greater attention needs to be paid to synthesizing these contributors.4 Psychological processes and socioenvironmental influences on pain have been well-documented for years,2,3,6,7 and even highlighted in recent articles from this very journal!8 Given the “biopsychosocial model of pain dominates the scientific community’s understanding of chronic pain”6 and provides important opportunities for optimizing treatment, we were disappointed to see only vague and over-simplified allusions to psychological and socioenvironmental pain contributors in the Younis et al. paper.1 We encourage the JPOSNA® readership at large to more deliberately consider these influences and related opportunities to enhance pain care for patients undergoing PSF, particularly given literature demonstrating comprehensive pain interventions are both cost-effective and yield better outcomes relative to traditional management.9 Pediatric health psychologists, as inherent experts on biopsychosocial care, are arguably some of the best-positioned specialists for integration into multidisciplinary management, whether in the form of routine preoperative behavioral health workup/clearance for PSF patients or as PRN postop care. While many medical specialties have routinely taken a multidisciplinary care approach for some time,10 it remains more the exception than the rule in pediatric orthopaedics – even in the face of literature repeatedly demonstrating prevalent behavioral health and psychosocial problems in context of AIS management/surgical intervention and related risk of postoperative complications like elevated acute pain, chronic pain, impairments in health-related quality of life, greater hospitalization length of stay and cost.2,11-16 Pediatric orthopaedics will do a great disservice to patients and families should we continue burying our heads in the sand, knowing there are critical opportunities to mitigate problems and address modifiable factors through the biopsychosocial lens.